THE EFFECT OF RETURN ON ASSET, RETURN ON EQUITY, NET PROFIT MARGIN, AND EARNING PER SHARE ON STOCK PRICE - Susilowati, Eko Meiningsih (Exsplorasi, 2015)
This research aimed to find out the effect of Return on Asset, Return on Equity, Net Profit Margin, and Earning per Share on stock price. This study employed secondary data from ISE. The population of research consisted of companies enlisted in Indonesian Stock Exchange. The sample used was food and beverage companies in 2008-2011 period. Technique of analyzing data used was regression analysis. The result of research showed that Return on Asset affected negatively and significantly the stock price, Return on Equity affected positively and significantly the stock price, Net Profit Margin affected positively and significantly the stock price, and Earning per share affected positively and significantly the stock price. Simultaneously the result was that Return on Asset, Return on Equity, Net Profit Margin, and Earning per Share simultaneously affected significantly the stock price.Keywords: Return on Asset, Return on Equity, Net Profit Margin, Earning per Share, and stock price